Performance of Mojosari Alabio Males Ducks Fed Complete Ration Silage - Ridla, Muhammad; Allaily, Allaily; Nikmah, Fitri Kurnia; Ramli, Nahrowi (ANIMAL PRODUCTION, 2014)
Abstract. The experiment was conducted to determine the effect of complete diet silage on feed consumption, body weight gain, feed conversion, water consumption and mortality. The materials used were 75 Mojosari Alabio male ducks, commercial diet plus rice bran (16.50% CP, 2900 kkal GE/kg), silage with 30-60% water content. Data were subject to Completely Randomized Design with five treatments and three replications. The treatments were S0 (commercial feed), S1 (silage with 30% water content), S2 (silage with 40% water content), S3 (silage with 50% water content) and S4 (silage with 60% water content). Data were subject to analysis of variance followed by orthogonal contrast test. The result showed that silage with 50% water content has significantly increased body weight gain and decreased water consumption, but there were no  effect in feed conversion. Complete diet silage was safe for Mojosari Alabio male duck. Key words : complete ration silage , duck, performance Abstrak. Penelitian ini untuk mengetahui pengaruh pemberian silase ransum komplit terhadap konsumsi pakan, pertambahan bobot badan, konversi pakan, konsumsi air dan persentase kematian. Bahan yang  digunakan adalah 75 ekor itik Mojosari Alabio jantan, ransum komersial ditambah dedak padi (16,50% CP, 2900 kkal GE/kg), silase dengan kadar air 30-60%. Percobaan ini menggunakan Rancangan Acak Lengkap dengan lima perlakuan dan tiga ulangan. Perlakuan S0 (pakan komersial), S1 (silase dengan kadar air 30%), S2 (silase dengan kadar air 40%), S3 (silase dengan kadar air 50%) dan S4 (silase dengan kadar air 60%). Data dianalisis menggunakan analisis ragam dan dilanjutkan dengan uji kontras orthogonal. Hasilnya menunjukkan bahwa silase dengan kadar air 50% memiliki peningkatan berat badan dan penurunan konsumsi air yang signifikan, tetapi tidak mempengaruhi konversi pakan. Silase ransum komplit pakan aman untuk itik Mojosari Alabio jantan. Kata kunci : silase ransum komplit, itik, performans